Garenoxacin in the treatment of community-acquired pneumonia - Biswas, Biswanath; Hajare, Anoop L.; Krishnaprasad, K.; Bhargava, Amit (International Journal of Basic & Clinical Pharmacology, 2017)
Community-acquired pneumonia (CAP) is a major cause of adult mortality in Asia. Empirical use of antibiotics depends on the pathogens that are commonly responsible. Evolution of resistant pathogens in CAP has added to the burden of treating physicians. Microbiological culture and antibiotic sensitivity testing are helpful for the treatment of such respiratory tract infections. Klebsiella pneumoniae though uncommon pathogen of CAP has been reported in many cases. Garenoxacin a newer fluoroquinolone has found its utility in the treatment of respiratory tract infections. Providing symptomatic relief to the patient with the use of analgesics, antipyretics and cough preparations are also an essential part of the management.